1985
DOI: 10.1097/00006842-198511000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psoriasis: psychoendocrine and metabolic reactions in psoriatic patients during standardized stressor exposure.

Abstract: Psychoendocrine and metabolic reactions during standardized stressor exposure (color-word conflict test and forced mental arithmetics) were studied in ten psoriatic and ten matched healthy subjects. During resting conditions, the groups were similar with regard to psychologic and biochemical variables, except for plasma glucose, which was slightly elevated in the psoriatic group. During stressor exposure, the psoriatic group reported significantly higher strain levels. Blood pressure, pulse rate, plasma glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
1
7

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 19 publications
8
71
1
7
Order By: Relevance
“…Acute stress is defined as stress that lasts for minutes to hours, and chronic stress is defined as stress that lasts for months to years (3). The psychophysiological stress response is an important modulator of skin immunobiology in health and disease (4)(5)(6)(7). Whereas chronic stress is immunosuppressive (8), studies have shown that acute stress enhances cutaneous immune function (6).…”
mentioning
confidence: 99%
“…Acute stress is defined as stress that lasts for minutes to hours, and chronic stress is defined as stress that lasts for months to years (3). The psychophysiological stress response is an important modulator of skin immunobiology in health and disease (4)(5)(6)(7). Whereas chronic stress is immunosuppressive (8), studies have shown that acute stress enhances cutaneous immune function (6).…”
mentioning
confidence: 99%
“…A kilenc, alapkortizolszintet vizsgáló tanulmányból öt alacsonyabb plazma-vagy nyálhormon-koncentrációt mutatott ki [16,53,54,55,56,57,58,59,60]. Tudva, hogy a HPA-tengely működését és így a kortizoltermelést fokozó IFN-γ, TNF-α, IL-10, IL-12 és IL-18 plazmaszintjei emelkedettek pikkelysömörben, a megfi gyelt alacsony stresszhormon-koncentráció diszfunkcionális HPA-tengely-működést sejtet [61].…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…Az alapszintmérések eredményei azonban ellentmondóak: míg Ionescu és mtsai (1991) emelkedett [64], addig Arnetz és mtsai (1985) [53] és Weigl (2000) normális hormonkoncentrációkról számolt be [60].…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…Chronic relapses of these plaques are known to occur and cause significant psychological distress upon these individuals [18]. Notably, the stress produced is connected to the inflammatory cascade by the neuroendocrine system, which shows a mechanism by which plaque psoriasis can progress [19]. Psoriatic patients experience episodes of intense stress that leads to changes in the serum cortisol levels and the pituitary-adrenocortical axis; such changes affect the regulatory mechanisms within the neuroendocrine system that leads to further progression of plaque psoriasis [19].…”
Section: Mental Health Of Individualsmentioning
confidence: 99%